2014
DOI: 10.1002/ange.201310712
|View full text |Cite
|
Sign up to set email alerts
|

Functionalizing Single Crystals: Incorporation of Nanoparticles Inside Gel‐Grown Calcite Crystals

Abstract: Synthetic single crystals are usually homogeneous solids. Biogenic single crystals, however, can incorporate biomacromolecules and become inhomogeneous solids so that their properties are also extrinsically regulated by the incorporated materials. The discrepancy between the properties of synthetic and biogenic single crystals leads to the idea to modify the internal structure of synthetic crystals to achieve nonintrinsic properties by incorporation of foreign material. Intrinsically colorless and diamagnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 52 publications
0
19
0
2
Order By: Relevance
“…[1][2][3][4][5][6][7][8] Taking inspiration from this biogenic strategy, the occlusion of nanoparticle additives within inorganic crystal hosts has recently gained increasing attention. [9][10][11][12][13][14][15] Not only do such synthetic routes provide a straightforward approach to the rational design of new hybrid materials with enhanced physical properties such as hardness, magnetism, color or strong fluorescence, [16][17][18][19][20] but they can also inform our understanding of biomineralization processes. [21][22][23][24] There is no doubt that the nanoparticle surface chemistry dictates their occlusion.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Taking inspiration from this biogenic strategy, the occlusion of nanoparticle additives within inorganic crystal hosts has recently gained increasing attention. [9][10][11][12][13][14][15] Not only do such synthetic routes provide a straightforward approach to the rational design of new hybrid materials with enhanced physical properties such as hardness, magnetism, color or strong fluorescence, [16][17][18][19][20] but they can also inform our understanding of biomineralization processes. [21][22][23][24] There is no doubt that the nanoparticle surface chemistry dictates their occlusion.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of guest species into host crystals has gained considerable interest because this bio-inspired strategy provides an attractive route for the preparation of new functional nanocomposites with tailored properties. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] However, the precise design rules for efficient and versatile nanoparticle occlusion within inorganic crystals remain elusive. For example, Pasteris and co-workers 16 reported that poly(acrylic acid)-stabilized micelles merely adsorbed onto the surface of sodium chloride crystals.…”
Section: Introductionmentioning
confidence: 99%
“…另一方面, 近年来的研究发现, 在将 功能性杂质引入单晶的过程中, 凝胶网络可以起到 媒介的关键作用. Liu等人 [27] 成 功 能 材 料 . 这 需 要 设 计 具 有 特 定 功 能 的 凝 胶 体 系 [59] , 也 需要逐步研究功能性的单晶 (如半导体晶 体 [51,52] Gel-grown method has been adopted to grow single crystals for over a century, and has triggered increasing interest with a large number of single crystals obtained.…”
Section: 体在硅胶中的生长 研究发现 Naf与kdp晶体能很unclassified
“…有趣的是, 虽然凝胶法作为一种常用的晶体生 长手段, 其悠久的历史可追溯到18世纪末 [25] , 但直 到1969年, 凝胶法生长晶体过程中凝胶网络能嵌入 单晶内部的现象才被发现并报道 [26] . 然而该现象仅 在一种晶体-凝胶体系中发现, 被认为可能是特例 [25] , 而不具有普遍意义, 因此在发表后较长的时间里并 如晶体-凝胶网络-粒子的复合体系, 为功能性第三组 分(如纳米粒子)的引入创造了便利 [27] , 从而为实现单 晶功能化提供了切实可行的途径和思路. 本文简要评 述了凝胶法制备凝胶网络-单晶复合物的研究进展.…”
unclassified